2001
DOI: 10.1002/1521-3803(20010601)45:3<206::aid-food206>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Determination of theMaillard product oxalic acidmonolysinylamide (OMA) in heated milk products by ELISA

Abstract: Oxalic acid monolysinylamide (OMA), a Maillard product which had initially been identified as a reaction product of L-ascorbic acid, was formed, dependent on the reaction conditions, also from other carbohydrate sources. At elevated temperatures and in the presence of oxygen, the reaction of lactose with proteins resulted in the formation of relatively high amounts of OMA. Using a polyclonal antibody, which bound with high specificity and affinity to OMA-modified proteins, a competitive enzyme linked immunosor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 19 publications
(27 reference statements)
2
9
0
Order By: Relevance
“…Oxalic acid monolysinylamide (OMA), a MRP of l-ascorbic acid, was detected in heat-treated milk products and commercial infant formulas using ELISA [147][148][149]. In this qualitative assay, a polyclonal antibody, which binds with high specificity and affinity to OMA-modified proteins, was used.…”
Section: Analysis Of Other Amino Acid Derivativesmentioning
confidence: 99%
“…Oxalic acid monolysinylamide (OMA), a MRP of l-ascorbic acid, was detected in heat-treated milk products and commercial infant formulas using ELISA [147][148][149]. In this qualitative assay, a polyclonal antibody, which binds with high specificity and affinity to OMA-modified proteins, was used.…”
Section: Analysis Of Other Amino Acid Derivativesmentioning
confidence: 99%
“…Samples were analyzed in triplicates. One Unit equals inhibition obtained with 1 µg/mL of CML-HSA or synthesized imidazolone-HSA (9).…”
Section: Chemicalsmentioning
confidence: 99%
“…To date, several techniques are applied for the detection and quantification of protein glycation products. Apart from chromatographic techniques including gas (7) and liquid chromatography (8), immmunochemical methods, mainly competitive ELISA (9), are used. Either of these techniques use secondary properties of particular Maillard products, such as fluorescence, UV-absorption, or affinity to highly specific antibodies, for identification and quantification.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, immunochemical methods have been successfully applied for analysis (9). In the course of these studies, various protein glycation products have been identified in model mixtures or in heated foodstuffs, and include the Amadori product, N -(carboxymethyl)lysine (1) (10), oxalic acid mono-N -lysinylamide (2) (11), pentosidine (12), or pyrraline (13). N -(carboxymethyl)lysine and oxalic acid mono-N -lysinylamide (9)(10)(11) have been used as markers for heat treatment of different food products.…”
Section: Introductionmentioning
confidence: 99%